2014
DOI: 10.4028/www.scientific.net/amm.656.280
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory Planning for Winding Carbon Wire of Composite Structures Using Cooperative Robots

Abstract: In this paper are presented aspects concerning robots trajectory planning for winding carbon wire around of a die, to obtain a composite structure which is used in automotive industry. One of the goals of the research is to realize parts using robots for creating one part and in the same time to optimize the cycle time comparing with manual method. Another goal of this study is to obtain a high accuracy of robot trajectory. This aspect is important because the shape of the final die is asymmetric and the robot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Two of the most important modeling methods of carbon fiber are considered: the placement method and especially the winding method. From the previous studies [20][21][22][23][24][25], it was observed that in the winding process the most important parameters are the trajectory, speeds, and especially tension of the fiber during the process.…”
mentioning
confidence: 99%
“…Two of the most important modeling methods of carbon fiber are considered: the placement method and especially the winding method. From the previous studies [20][21][22][23][24][25], it was observed that in the winding process the most important parameters are the trajectory, speeds, and especially tension of the fiber during the process.…”
mentioning
confidence: 99%